Identification of the powdery mildew resistance gene in wheat breeding line Yannong 99102-06188 via bulked segregant exome capture sequencing - Mu, Yanjun; Gong, Wenping; Qie, Yanmin; Liu, Xueqing; Li, Linzhi; Sun, Nina; Liu, Wei; Guo, Jun; Han, Ran; Yu, Ziyang; Xiao, Luning; Su, Fuyu; et al. (Frontiers in Plant Science, 2022)
Powdery mildew of wheat (Triticum aestivum), caused by Blumeria graminis f. sp. tritici (Bgt), is a destructive disease that seriously threatens the yield and quality of its host. Identifying resistance genes is the most attractive and effective strategy for developing disease-resistant cultivars and controlling this disease. In this study, a wheat breeding line Yannong 99102-06188 (YN99102), an elite derivative line from the same breeding process as the famous wheat cultivar Yannong 999, showed high resistance to powdery mildew at the whole growth stages. Genetic analysis was carried out using Bgt isolate E09 and a population of YN99102 crossed with a susceptible parent Jinhe 13-205 (JH13-205). The result indicated that a single recessive gene, tentatively designated pmYN99102, conferred seedling resistance to the Bgt isolate E09. Using bulked segregant exome capture sequencing (BSE-Seq), pmYN99102 was physically located to a ~33.7 Mb (691.0-724.7 Mb) interval on the chromosome arm 2BL, and this interval was further locked in a 1.5 cM genetic interval using molecular markers, which was aligned to a 9.0 Mb physical interval (699.2-708.2 Mb). Based on the analysis of physical location, origin, resistant spectrum, and inherited pattern, pmYN99102 differed from those of the reported powdery mildew (Pm) resistance genes on 2BL, suggesting pmYN99102 is most likely a new Pm gene/allele in the targeted interval. To transfer pmYN99102 to different genetic backgrounds using marker-assisted selection (MAS), 18 closely linked markers were tested for their availability in different genetic backgrounds for MAS, and all markers expect for YTU103-97 can be used in MAS for tracking pmYN99102 when it transferred into those susceptible cultivars.